Programmes and Activities of the Department of Information and Knowledge Technology in College of Arts- University of Basra: An Analytical Study - Abdul Rahman Abdul Wahid , Prof. Dr. Amal; Neamah Abdul Qader, Assist. Lect . Nidhal (Basra studies journal, 2026)
The research aims to introduce the programs and activities that the mentioned department held for the academic years (2022-2025) for three consecutive years and to introduce the time distribution of the various activities represented in conferences, seminars, discussion panels, workshops, training courses and other activities, as they have an effective role in raising the level of faculty members and developing their skills in research and teaching, as well as raising students’ awareness of many matters that will help them in their future academic and professional lives. These activities varied during the three years and amounted to be (99) scientific activities. The documentary method was adopted when preparing the theoretical part, as well as adopting the descriptive analytical method in the practical part. The data and information for the research were collected by relying on the scientific plans for the three years that are available in the department, as well as interviewing the officials of the Studies and Planning Division to obtain information that is difficult to obtain from the scientific plans in the department.